Epigenetic alterations in salivary gland neoplasms and the impact of these alterations in tumor progression and prognosis: A systematic review and meta-analysis - Karolina Skarlet Silva Viana; Mariana Saturnino de Noronha; Cristiane Squarize; Lucas Guimarães Abreu; Maria Cássia Ferreira Aguiar; Vanessa Fátima Bernardes (Oral Oncology Reports)
Salivary gland tumors (SGTs) are uncommon lesions with etiologic factors not clearly defined. Epigenetic alterations have been suggested as one of the etiologic factors and as a possible factor impacting the prognosis of SGTs. The epigenetic alterations might include DNA methylation, alterations on the expression of noncoding RNAs and structural modification of histones. The aim of this study was to evaluate the available evidence about the epigenetic alterations associated to SGTs and their possible role on prognosis of SGTs. A Systematic Review was conducted according to PRISMA statement and prospectively registered on PROSPERO (CRD42022325647). The PECO question was “What are the epigenetic alterations in salivary gland neoplasms and their role in the progression and the prognosis of the tumor?“. A search strategy was elaborated to retrieve studies able to answer this question and applied to each database: PubMed, Web of Science and Scopus, as well as the Grey Literature. Two independent reviewers worked in all steps. The search comprised a total of 1807 studies and after removal according to inclusion and exclusion criteria, 47 studies were included in this systematic review. The Joana Briggs Institute tool was used for appraisal of methodological quality of studies. A meta-analysis was conducted for methylation regarding the genes MGMT and RASSF1A and found that both genes methylation is related to higher stages of the SGTs but did not show an association with grade of tumors. The results must be evaluated carefully, once GRADE showed a very low certainty of evidence.